Combined therapy with Luteinizing Hormone Releasing Hormone agonist (LHRHa) and Growth Hormone (GH) in central precocious puberty - Volta, C.; Regazzi, C.; Ndaka, et al., J. (Acta Biomedica Atenei Parmensis, 2005)
Luteinizing Hormone Releasing Hormone analogues (LHRHa) are considered the treatment of choice in central precocious puberty (CPP). Final height after therapy is usually higher than the predicted one before treatment, but about 60% of patients do not reach their genetic target. The association of Growth Hormone (GH) with LHRHa could be useful in a subgroup of children with CPP and low growth velocity in order to obtain a higher final height with a complete expression of genetic potential. Moreover, in children with early puberty adopted from developing countries, predicted adult height is significantly greater when the combined therapy, GH and LHRHa, is employed. In this paper the rationale for adding GH to LHRHa is discussed and the clinical reports from the literature are presented.